Plastic surface waterproof plywood and production method thereof
By preparing a modified MMT grafted SiO2 coating on the surface of plastic-surface plywood, using sol-gel method and hydrophobic modifier, the problem of poor hydrophobic performance of existing plastic-surface plywood is solved, and efficient superhydrophobic performance is achieved. Mechanical durability reduces the harm to human health.
Patent Information
- Application Number
- CN202411220719.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-17
AI Technical Summary
The existing plastic-surface plywood has poor hydrophobic properties and flame retardant properties, which are prone to stains, and due to the potential harm of fluorine compounds, it seeks low-cost and environmentally friendly alternative materials.
SiO2 was grown in situ on the surface of sodium montmorillonite by sol-gel method, and the modified SiO2 particles were hydrophobically modified by octadecyltrimethoxysilane and octadecyltrimethylammonium bromide, and combined with poly Dimethylsiloxane modified epoxy resin prepares a superhydrophobic coating to form modified MMT grafted SiO2 as a reinforced phase to improve the mechanical durability and hydrophobic properties of the coating.
It effectively improves the superhydrophobic properties of plastic surface waterproof plywood, reduces the harm to human health, enhances the mechanical durability and solvent resistance of the coating, and avoids the use of fluorine compounds.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of plywood, and more particularly to a plastic-surface waterproof plywood and a production method thereof. Background Art
[0002] Plywood is a three-layer or multi-layer plate material made by peeling wood segments into veneers or planing wood blocks into thin wood, and then gluing them with adhesives. It is usually made of an odd number of veneers, and the fibers of adjacent veneers are glued perpendicular to each other. Plywood is one of the commonly used materials for furniture, one of the three major artificial boards, and can also be used as materials for airplanes, ships, trains, cars, buildings, and packaging boxes. The names of the layers of plywood are: the surface veneer is called the surface board, and the inner veneer is called the core board; the front surface board is called the front board, and the back surface board is called the back board; in the core board, the fiber direction is parallel to the surface board is called the long core board or the middle board. When forming the cavity table board blank, the front board and the back board must face outward. The plastic-faced plywood in plywood is mainly to set a plastic surface layer on the plywood panel. The plastic surface layer is generally made of PVC or EVA. Although it also has waterproof properties, its surface hydrophobicity and flame retardant properties are poor, and it is easy to be stained in actual use.
[0003] Low surface energy and micro-nanostructure are two indispensable factors in constructing artificial super-hydrophobic surfaces. Fluorine compounds, as the materials with the lowest surface energy, are widely used to prepare super-hydrophobic surfaces. However, the use of fluorine compounds is greatly restricted due to the high cost of raw materials and potential harm to human health. Long carbon chain compounds and silicon-oxygen polymers have attracted widespread attention due to their low cost, non-toxicity and environmental protection, and are regarded as ideal substitutes for fluorine-free low surface energy materials. Summary of the invention
[0004] In order to overcome the above-mentioned defects of the prior art, an embodiment of the present invention provides a plastic-faced waterproof plywood and a production method thereof.
[0005] A plastic-faced waterproof plywood is provided. A hydrophobic coating is prepared on the surface of the plastic-faced waterproof plywood. The raw materials of the hydrophobic coating include, by weight percentage, 6.5-7.5% of polydimethylsiloxane, 19-21% of a curing agent, 19-21% of a modified filler, and the rest is epoxy resin.
[0006] Furthermore, the curing agent is one of m-phenylenediamine, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and diethylaminopropylamine.
[0007] Furthermore, the modified filler includes: tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide, octadecyltrimethoxysilane and octadecyltrimethylammonium bromide; the weight ratio of tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane is 1: (1.1-1.5): (3.0-3.7): (0.06-0.10); the amount of octadecyltrimethylammonium bromide is 1.3-1.5 times the cation exchange capacity (CEC) of sodium montmorillonite.
[0008] Furthermore, the raw materials of the hydrophobic coating include, by weight percentage: 6.8-7.2% of polydimethylsiloxane, 19.5-20.5% of a curing agent, 19.5-20.5% of a modified filler, and the rest is an epoxy resin; the weight ratio of the tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane is 1:(1.2-1.4):(3.2-3.5):(0.07-0.09); the amount of the octadecyltrimethylammonium bromide is 1.35-1.45 times the cation exchange capacity (CEC) of sodium montmorillonite.
[0009] Furthermore, the raw materials of the hydrophobic coating include, by weight percentage: 7.0% of polydimethylsiloxane, 20% of a curing agent, 20% of a modified filler, and the rest is an epoxy resin; the tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane are in a weight ratio of 1:1.3:3.35:0.08; the amount of octadecyltrimethylammonium bromide is 1.4 times the cation exchange capacity (CEC) of sodium montmorillonite.
[0010] A production method of plastic-faced waterproof plywood, the specific production steps are as follows:
[0011] Step 1: Weigh polydimethylsiloxane, curing agent, epoxy resin, ethyl orthosilicate, sodium montmorillonite, ammonium hydroxide, octadecyltrimethoxysilane and octadecyltrimethylammonium bromide in the modified filler raw materials;
[0012] Step 2: adding sodium montmorillonite and ammonium hydroxide to anhydrous ethanol and ultrasonically treating for 10 to 20 minutes; adding ethyl orthosilicate to anhydrous ethanol to dilute and then adding to the above solution to stand for 8 to 12 minutes, stirring magnetically to react for 5 to 7 hours, and then filtering and drying to obtain a mixture A;
[0013] Step 3: Add mixed material A to deionized water, perform ultrasonic treatment for 20 to 40 minutes, then add ammonia water dropwise to adjust the pH to 12, and perform magnetic stirring to obtain a suspension;
[0014] Step 4: adding octadecyltrimethoxysilane to anhydrous ethanol, and subjecting the mixture to ultrasonic treatment for 10 to 20 minutes to obtain a solution B; adding octadecyltrimethylammonium bromide to deionized water, and subjecting the mixture to ultrasonic treatment for 10 to 20 minutes to obtain a solution C;
[0015] Step 5: adding solution B and solution C to the suspension, stirring in a water bath for 5 to 7 hours, washing, centrifuging, filtering, drying, and grinding to obtain a modified filler;
[0016] Step 6: After mixing polydimethylsiloxane, curing agent, epoxy resin and modified filler, add them into ethanol solution and stir for 50 to 70 minutes to form a uniform spray solution;
[0017] Step 7: spray the spray liquid onto the surface of the plastic surface waterproof plywood, and cure it at 55-65° C. for 3-5 hours to form a hydrophobic coating on the surface of the plastic surface waterproof plywood to obtain a super hydrophobic plastic surface waterproof plywood.
[0018] Furthermore, in step 2, the weight ratio of sodium montmorillonite to anhydrous ethanol is 1:20-30, the weight ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:20-30, the ultrasonic frequency is 1.2-1.6 MHz, the ultrasonic power is 400-600 W, and the magnetic stirring speed is 400-600 r / min; in step 3, the weight ratio of mixture A to deionized water is 1:100-150, the ultrasonic frequency is 1.2-1.6 MHz, the ultrasonic power is 400-600 W, and the magnetic stirring speed is 400-600 r / min.
[0019] Furthermore, in step 4, the weight ratio of octadecyltrimethoxysilane to anhydrous ethanol is 1:10-20, the weight ratio of octadecyltrimethylammonium bromide to deionized water is 1:10-20, the ultrasonic frequency is 1.2-1.6 MHz, and the ultrasonic power is 400-600 W; in step 5, the water bath temperature is 55-65° C., the stirring speed is 200-400 r / min, and the ethanol solution is used for multiple washings.
[0020] Furthermore, in step six, the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and modified filler to the ethanol solution is 5.4-6.0:1; in step seven, the spraying pressure is 0.55-0.65 MPa.
[0021] Further, in step 2, the weight ratio of sodium montmorillonite to anhydrous ethanol is 1:25, the weight ratio of ethyl orthosilicate to anhydrous ethanol is 1:25, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 3, the weight ratio of mixture A to deionized water is 1:125, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 4, octadecyl trimethoxy silane and anhydrous ethanol are added. The weight ratio of water to ethanol is 1:15, the weight ratio of octadecyltrimethylammonium bromide to deionized water is 1:15, the ultrasonic frequency is 1.4 MHz, and the ultrasonic power is 500 W; in step five, the water bath temperature is 60° C., the stirring speed is 300 r / min, and the ethanol solution is used for multiple washings during washing; in step six, the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and modified filler to the ethanol solution is 5.7:1; in step seven, the spraying pressure is 0.60 MPa.
[0022] Technical effects and advantages of the present invention:
[0023] 1. The plastic surface waterproof plywood prepared by the raw material formula of the present invention can effectively improve its surface hydrophobicity, and no fluorine compounds are used in the raw materials, which can effectively improve the super hydrophobicity of the surface of the plastic surface waterproof plywood and effectively reduce the harm of the super hydrophobic surface to human health; SiO2 with good internal interface strength is in situ grown on the surface of sodium montmorillonite (MMT) by a sol-gel method. 2 , and MMT-grafted SiO 2( Note: MMT-SiO 2 Particles), octadecyl trimethyl ammonium bromide cationic modifier was used to graft MMT onto SiO 2 The particles were intercalated and hydrophobically modified, and octadecyltrimethoxysilane was used to graft MMT onto SiO 2 The particle surface was hydrophobically modified to obtain modified MMT-grafted SiO 2 ; Modified MMT grafted SiO 2 As the reinforcing phase, polydimethylsiloxane modified epoxy resin (EP / PDMS) was used as the matrix to prepare the super hydrophobic coating; in situ grown nano-SiO 2 Enhanced nano-SiO 2 Interface stability with MMT surface, hydrophobic MMT-grafted SiO 2 Nano-SiO2 grown in situ on the surface of sodium montmorillonite 2 The synergistic effect can reduce the solid-liquid contact area and the in-situ grown SiO 2 The strong interfacial interaction provided on the MMT surface can significantly improve the mechanical durability of the coating;
[0024] 2. The present invention adopts the sol-gel method to ultrasonically disperse sodium montmorillonite and ammonium hydroxide in anhydrous ethanol to form a uniform mixed solution; ethyl orthosilicate is diluted with anhydrous ethanol and added to the mixed solution for static treatment, and then hydrolyzed under magnetic stirring and filtered and dried to obtain nano sodium montmorillonite grafted SiO 2 ; Grafting nano-sodium montmorillonite onto SiO 2 The mixture was ultrasonically dispersed in deionized water, and then the pH value of the reaction solution was adjusted to provide suitable reaction conditions for subsequent reactions; octadecyltrimethoxysilane was added to anhydrous ethanol for ultrasonic treatment to obtain solution B, and octadecyltrimethylammonium bromide was added to deionized water for ultrasonic treatment to obtain solution C. The reaction solution was prepared in advance to facilitate the uniformity and stability of the distribution of the raw materials in the subsequent reactions; solution B and solution C were added to the suspension, stirred in a water bath, washed, centrifuged, filtered, dried, and ground to obtain the modified MMT grafted SiO 2 During the water bath stirring process, octadecyl trimethyl ammonium bromide was used to graft MMT onto SiO 2 The particles were treated with intercalation modification, and octadecyltrimethoxysilane was hydrolyzed and MMT was grafted onto SiO 2 SiO in particles 2 The surface is hydrophobically modified. DETAILED DESCRIPTION
[0025] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1:
[0027] The present invention provides a plastic-faced waterproof plywood, on the surface of which a hydrophobic coating is prepared, wherein the raw materials of the hydrophobic coating include, by weight percentage, 6.5% of polydimethylsiloxane, 19% of metaphenylenediamine, 19% of modified filler, and 55.5% of epoxy resin;
[0028] The modified filler comprises: tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide, octadecyl trimethoxysilane and octadecyl trimethyl ammonium bromide; the tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyl trimethoxysilane are in a weight ratio of 1:1.1:3.0:0.06; the amount of octadecyl trimethyl ammonium bromide is 1.3 times the cation exchange capacity (CEC) of sodium montmorillonite, and the amount of octadecyl trimethyl ammonium bromide is used in a molar ratio of the cation exchange capacity (CEC) of sodium montmorillonite;
[0029] Sodium montmorillonite (cation exchange capacity of 1.26 mmol / g), tetraethyl orthosilicate, and epoxy resin (EP, solid content 40%) were purchased from Shanghai MacLean Biochemical Co., Ltd.; polydimethylsiloxane was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S26896; m-phenylenediamine was purchased from Hubei Chengfeng Chemical Co., Ltd.; ammonium hydroxide was purchased from Hubei Chengfeng Chemical Co., Ltd., mass fraction 25%; octadecyltrimethoxysilane was purchased from Hubei Chengfeng Chemical Co., Ltd.; octadecyltrimethylammonium bromide was purchased from Hubei Chengfeng Chemical Co., Ltd.;
[0030] The production method of plastic-faced waterproof plywood includes the following specific production steps:
[0031] Step 1: Weigh polydimethylsiloxane, curing agent, epoxy resin, ethyl orthosilicate, sodium montmorillonite, ammonium hydroxide, octadecyltrimethoxysilane and octadecyltrimethylammonium bromide in the modified filler raw materials;
[0032] Step 2: adding sodium montmorillonite and ammonium hydroxide to anhydrous ethanol and ultrasonically treating for 15 minutes; adding tetraethyl orthosilicate to anhydrous ethanol to dilute and then adding to the above solution to stand for 10 minutes, magnetically stirring for 6 hours, filtering and drying to obtain a mixture A; the weight ratio of sodium montmorillonite to anhydrous ethanol is 1:20, the weight ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:20, the ultrasonic frequency is 1.2MHz, the ultrasonic power is 400W, and the magnetic stirring speed is 400r / min;
[0033] Step 3: Add mixed material A to deionized water, perform ultrasonic treatment for 30 minutes, then add ammonia water dropwise to adjust the pH to 12, and perform magnetic stirring treatment to obtain a suspension; the weight ratio of mixed material A to deionized water is 1:100, the ultrasonic frequency is 1.2 MHz, the ultrasonic power is 400 W, and the magnetic stirring speed is 400 r / min;
[0034] Step 4: adding octadecyltrimethoxysilane to anhydrous ethanol, and ultrasonically treating for 15 minutes to obtain solution B; adding octadecyltrimethylammonium bromide to deionized water, and ultrasonically treating for 15 minutes to obtain solution C; the weight ratio of octadecyltrimethoxysilane to anhydrous ethanol is 1:10, the weight ratio of octadecyltrimethylammonium bromide to deionized water is 1:10, the ultrasonic frequency is 1.2 MHz, and the ultrasonic power is 400 W;
[0035] Step 5: adding solution B and solution C to the suspension, stirring in a water bath for 6 hours, washing, centrifuging, filtering, drying, and grinding to obtain a modified filler; the water bath temperature is 55°C, the stirring speed is 200r / min, and the ethanol solution is used for multiple washings; centrifuging until the upper clear liquid is used with a 0.1mol / L silver nitrate solution until no impurity ions such as Br- and Cl- can be detected;
[0036] Step 6: After mixing polydimethylsiloxane, curing agent, epoxy resin and modified filler, add them into ethanol solution and stir for 60 minutes to form a uniform spray liquid; the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and modified filler to the weight of the ethanol solution is 5.4:1;
[0037] Step seven: spray the spray liquid onto the surface of the plastic surface waterproof plywood at a spray pressure of 0.55 MPa, and cure it at 60° C. for 4 hours to form a hydrophobic coating on the surface of the plastic surface waterproof plywood to obtain a super hydrophobic plastic surface waterproof plywood.
[0038] Embodiment 2:
[0039] Different from Example 1, the raw materials of the hydrophobic coating include, by weight percentage: 7.5% polydimethylsiloxane, 21% m-phenylenediamine, 21% modified filler, and 50.5% epoxy resin; the weight ratio of the tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane is 1:1.5:3.7:0.10; the amount of octadecyltrimethylammonium bromide is 1.5 times the cation exchange capacity (CEC) of sodium montmorillonite.
[0040] Embodiment 3:
[0041] Different from Examples 1-2, the raw materials of the hydrophobic coating include, by weight percentage: 7.0% polydimethylsiloxane, 20% curing agent, 20% modified filler, and 53% epoxy resin; the weight ratio of the tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane is 1:1.3:3.35:0.08; the amount of octadecyltrimethylammonium bromide is 1.4 times the cation exchange capacity (CEC) of sodium montmorillonite.
[0042] Embodiment 4:
[0043] The difference from Example 3 is that in step 2, the weight ratio of sodium montmorillonite to anhydrous ethanol is 1:25, the weight ratio of ethyl orthosilicate to anhydrous ethanol is 1:25, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 3, the weight ratio of mixture A to deionized water is 1:125, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 4, octadecyl trimethoxysilane The weight ratio of alkane to anhydrous ethanol is 1:15, the weight ratio of octadecyltrimethylammonium bromide to deionized water is 1:15, the ultrasonic frequency is 1.4MHz, and the ultrasonic power is 500W; in step five, the water bath temperature is 60°C, the stirring speed is 300r / min, and the ethanol solution is used for multiple washings during washing; in step six, the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and modified filler to the ethanol solution is 5.7:1; in step seven, the spraying pressure is 0.60MPa.
[0044] Comparative Example 1:
[0045] The difference from Example 4 is that the raw materials of the hydrophobic coating include, by weight percentage, 7.0% polydimethylsiloxane, 20% curing agent, 20% modified filler, and 53% epoxy resin; the modified filler is sodium montmorillonite;
[0046] After mixing polydimethylsiloxane, curing agent, epoxy resin and sodium montmorillonite, the mixture was added into an ethanol solution and stirred for 60 minutes to form a uniform spray solution; the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and sodium montmorillonite to the ethanol solution was 5.7:1;
[0047] The spraying liquid is sprayed onto the surface of the plastic-faced waterproof plywood, and cured at 60° C. for 4 hours to prepare a hydrophobic coating on the surface of the plastic-faced waterproof plywood to obtain a super-hydrophobic plastic-faced waterproof plywood; the spraying pressure is 0.60 MPa.
[0048] Comparative Example 2:
[0049] The difference from Example 4 is that the raw materials of the hydrophobic coating include, by weight percentage, 7.0% polydimethylsiloxane, 20% curing agent, 20% modified filler, and 53% epoxy resin; the modified filler includes nano-silicon dioxide;
[0050] After mixing polydimethylsiloxane, curing agent, epoxy resin and nano-silicon dioxide, adding the mixture into an ethanol solution and stirring for 60 minutes to form a uniform spraying liquid; the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and nano-silicon dioxide to the ethanol solution is 5.7:1;
[0051] The spraying liquid is sprayed onto the surface of the plastic-faced waterproof plywood, and cured at 60° C. for 4 hours to prepare a hydrophobic coating on the surface of the plastic-faced waterproof plywood to obtain a super-hydrophobic plastic-faced waterproof plywood; the spraying pressure is 0.60 MPa.
[0052] Comparative Example 3:
[0053] The difference from Example 4 is that the raw materials of the hydrophobic coating include, by weight percentage, 7.0% polydimethylsiloxane, 20% curing agent, 20% modified filler, and 53% epoxy resin; the modified filler includes: tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethylammonium bromide; the tetraethyl orthosilicate, sodium montmorillonite and ammonium hydroxide are in a weight ratio of 1:1.3:3.35; the amount of octadecyltrimethylammonium bromide is 1.4 times the cation exchange capacity (CEC) of sodium montmorillonite.
[0054] The production method of plastic-faced waterproof plywood includes the following specific production steps:
[0055] Step 1: Weigh polydimethylsiloxane, curing agent, epoxy resin, ethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethylammonium bromide in the modified filler raw materials;
[0056] Step 2: adding sodium montmorillonite and ammonium hydroxide to anhydrous ethanol and ultrasonically treating for 15 minutes; adding ethyl orthosilicate to anhydrous ethanol to dilute and then adding to the above solution to stand for 10 minutes, stirring magnetically to react for 6 hours, filtering and drying to obtain a mixture A;
[0057] Step 3: Add mixed material A to deionized water, perform ultrasonic treatment for 30 minutes, then add ammonia water dropwise to adjust the pH to 12, and perform magnetic stirring to obtain a suspension;
[0058] Step 4: adding octadecyltrimethylammonium bromide to deionized water and performing ultrasonic treatment for 15 minutes to obtain solution C;
[0059] Step 5: adding solution C to the suspension, stirring in a water bath for 6 hours, washing, centrifuging, filtering, drying, and grinding to obtain a modified filler;
[0060] Step 6: After mixing polydimethylsiloxane, curing agent, epoxy resin and modified filler, add them into ethanol solution and stir for 60 minutes to form a uniform spray solution;
[0061] Step 7: spraying the spraying liquid onto the surface of the plastic surface waterproof plywood, curing at 60° C. for 4 hours, preparing a hydrophobic coating on the surface of the plastic surface waterproof plywood, and obtaining a super hydrophobic plastic surface waterproof plywood;
[0062] In step 2, the weight ratio of sodium montmorillonite to anhydrous ethanol is 1:25, the weight ratio of tetraethyl orthosilicate to anhydrous ethanol is 1:25, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 3, the weight ratio of mixture A to deionized water is 1:125, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 4, the weight ratio of octadecyltrimethylammonium bromide to deionized water is 1:15, the ultrasonic frequency is 1.4 MHz, and the ultrasonic power is 500 W; in step 5, the water bath temperature is 60° C., the stirring speed is 300 r / min, and ethanol solution is used for multiple washing during washing; in step 6, the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and modified filler to the ethanol solution is 5.7:1; in step 7, the spraying pressure is 0.60 MPa.
[0063] The plastic-faced waterproof plywood in the comparative example and the embodiment of the present invention was tested and processed:
[0064] The contact angle and rolling angle of the coating were measured using a contact angle meter. Six locations on the coating surface were tested and the results were averaged.
[0065] The results are shown in Table 1:
[0066] Table 1:
[0067] Contact angle (°) Roll angle (°) Comparative Example 1 141.3±1.1 27.4±1.8 Comparative Example 2 134.7±1.2 29.8±1.8 Comparative Example 3 152.6±1.2 9.1±0.6 Example 1 154.8±1.1 8.6±0.5 Example 2 155.0±1.2 8.5±0.5 Example 3 155.2±1.0 8.2±0.4 Example 4 155.6±1.0 8.2±0.4
[0068] It can be seen from the above table that the plastic-faced waterproof plywood of the present invention can effectively improve its surface hydrophobicity, and no fluorine compounds are used in the raw materials, which can effectively improve the super-hydrophobicity of the surface of the plastic-faced waterproof plywood and effectively reduce the harm of the super-hydrophobic surface to human health.
[0069] The present invention adopts a sol-gel method to in-situ grow SiO2 with good internal interface strength on the surface of sodium montmorillonite (MMT) 2 , and MMT-grafted SiO 2( Note: MMT-SiO 2 Particles), octadecyl trimethyl ammonium bromide cationic modifier was used to graft MMT onto SiO 2 The particles were intercalated and hydrophobically modified, and octadecyltrimethoxysilane was used to graft MMT onto SiO 2 The particle surface was hydrophobically modified to obtain modified MMT-grafted SiO 2 ; Modified MMT grafted SiO 2 As the reinforcing phase, polydimethylsiloxane-modified epoxy resin (EP / PDMS) was used as the matrix to prepare the superhydrophobic coating;
[0070] Nano-SiO2 Composite with sodium montmorillonite can bring into play the synergistic effect of the two and improve the nano-SiO 2 The MMT grafted SiO synthesized by sol-gel method 2 The particle surface presents a dense micro / nano structure; the in-situ grown SiO 2 The strong interfacial interaction provided on the MMT surface can significantly improve the mechanical durability of the coating; the hydrolysis of ethyl orthosilicate generates nano-SiO 2 Precursor, through the condensation reaction of Si-OH and Al-OH, nano-SiO 2 It can be grafted onto two-dimensional MMT; during the hydrolysis of ethyl orthosilicate, not only SiO 2 The sol particles undergo polycondensation reaction, SiO 2 A polycondensation reaction also occurred between the sol particles and the hydroxyl groups on the surface of MMT. 2 In-situ growth on the MMT surface through chemical bonds;
[0071] The interlayer cations of sodium montmorillonite can undergo a strong ion exchange reaction with octadecyl trimethyl ammonium bromide, which completely opens the layer structure of sodium montmorillonite. The modifier octadecyl trimethyl ammonium bromide is inserted into the interlayer of sodium montmorillonite, which expands the interlayer distance of sodium montmorillonite, facilitates the entry of polymers into the interlayers of sodium montmorillonite, and improves the dispersion stability of the reinforcing phase in the matrix. After modification with octadecyl trimethyl ammonium bromide, the hydrophobic MMT grafted SiO 2 Nano-SiO2 grown in situ on the surface of sodium montmorillonite 2 The synergistic effect can reduce the solid-liquid contact area and capture more gas than the unmodified sodium montmorillonite. 2 Enhanced nano-SiO 2 The interface stability with the MMT surface improves the hardness of the coating, and the nano-SiO 2 The in-situ growth on the surface of sodium montmorillonite forms a porous nanostructure. The micro / nano porous rough structure captures air to form cavities, making it impossible for organic solvents to penetrate into the coating. Therefore, the composite coating has better solvent resistance and exhibits super hydrophobic durability. 2 While the particles were being intercalated, octadecyltrimethoxysilane and MMT were grafted onto SiO 2 SiO in particles 2 The surface is hydrophobic modified to further improve the super-hydrophobic properties of the coating;
[0072] In step 2, sodium montmorillonite and ammonium hydroxide are ultrasonically dispersed in anhydrous ethanol to form a uniform mixed solution by using a sol-gel method; ethyl orthosilicate is diluted with anhydrous ethanol and added to the mixed solution, and then the solution is allowed to stand for treatment, and then hydrolyzed under magnetic stirring and filtered and dried to obtain a mixture A (nano sodium montmorillonite grafted SiO 2 ); In step three, the nano sodium montmorillonite is grafted onto SiO 2 Ultrasonic dispersion treatment is performed in deionized water, and then the pH value of the reaction solution is adjusted to provide suitable reaction conditions for subsequent reactions; in step 4, octadecyltrimethoxysilane is added to anhydrous ethanol for ultrasonic treatment to obtain solution B, and octadecyltrimethylammonium bromide is added to deionized water for ultrasonic treatment to obtain solution C, and the reaction solution of octadecyltrimethoxysilane and octadecyltrimethylammonium bromide is prepared in advance to facilitate the uniformity and stability of the distribution of the raw materials in the subsequent reaction; in step 5, solution B and solution C are added to the suspension, stirred in a water bath, washed, centrifuged, filtered, dried, and ground to obtain a modified filler (modified MMT grafted SiO 2 ), in the process of stirring in a water bath, octadecyl trimethyl ammonium bromide was used to graft MMT onto SiO 2 The particles were treated with intercalation modification, and octadecyltrimethoxysilane was hydrolyzed and MMT was grafted onto SiO 2 SiO in particles 2 The surface is subjected to hydrophobic modification treatment; in step six, polydimethylsiloxane, curing agent, epoxy resin and modified filler are mixed, added into ethanol solution, stirred and dispersed, and a spray liquid is prepared; in step seven, the spray liquid is sprayed onto the surface of the plastic surface waterproof plywood, and a hydrophobic coating is prepared on the surface of the plastic surface waterproof plywood after curing to obtain a super hydrophobic plastic surface waterproof plywood.
[0073] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A plastic-faced waterproof plywood, characterized in that: A hydrophobic coating is prepared on the surface of a plastic-faced waterproof plywood. The raw materials of the hydrophobic coating include, by weight percentage, 6.5-7.5% of polydimethylsiloxane, 19-21% of a curing agent, 19-21% of a modified filler, and the rest is epoxy resin.
2. The plastic-faced waterproof plywood according to claim 1, characterized in that: The curing agent is one of m-phenylenediamine, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and diethylaminopropylamine.
3. The plastic-faced waterproof plywood according to claim 2, characterized in that: The modified filler comprises: tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide, octadecyltrimethoxysilane and octadecyltrimethylammonium bromide; the weight ratio of tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane is 1:(1.1-1.5):(3.0-3.7):(0.06-0.10); the amount of octadecyltrimethylammonium bromide is 1.3-1.5 times the cation exchange capacity (CEC) of sodium montmorillonite.
4. The plastic-faced waterproof plywood according to claim 3, characterized in that: The raw materials of the hydrophobic coating include, by weight percentage: 6.8-7.2% of polydimethylsiloxane, 19.5-20.5% of a curing agent, 19.5-20.5% of a modified filler, and the rest is an epoxy resin; the weight ratio of the tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane is 1:(1.2-1.4):(3.2-3.5):(0.07-0.09); the amount of the octadecyltrimethylammonium bromide is 1.35-1.45 times the cation exchange capacity (CEC) of the sodium montmorillonite.
5. The plastic-faced waterproof plywood according to claim 3, characterized in that: The raw materials of the hydrophobic coating include, by weight percentage: 7.0% of polydimethylsiloxane, 20% of a curing agent, 20% of a modified filler, and the rest being epoxy resin; the tetraethyl orthosilicate, sodium montmorillonite, ammonium hydroxide and octadecyltrimethoxysilane are in a weight ratio of 1:1.3:3.35:0.08; and the amount of octadecyltrimethylammonium bromide is 1.4 times the cation exchange capacity (CEC) of sodium montmorillonite.
6. A method for producing plastic-faced waterproof plywood, characterized in that: The specific production steps are as follows: Step 1: Weigh polydimethylsiloxane, curing agent, epoxy resin, ethyl orthosilicate, sodium montmorillonite, ammonium hydroxide, octadecyltrimethoxysilane and octadecyltrimethylammonium bromide in the modified filler raw materials; Step 2: adding sodium montmorillonite and ammonium hydroxide to anhydrous ethanol and ultrasonically treating for 10 to 20 minutes; adding ethyl orthosilicate to anhydrous ethanol to dilute and then adding to the above solution to stand for 8 to 12 minutes, stirring magnetically to react for 5 to 7 hours, and then filtering and drying to obtain a mixture A; Step 3: Add mixed material A to deionized water, perform ultrasonic treatment for 20 to 40 minutes, then add ammonia water dropwise to adjust the pH to 12, and perform magnetic stirring to obtain a suspension; Step 4: adding octadecyltrimethoxysilane to anhydrous ethanol, and subjecting the mixture to ultrasonic treatment for 10 to 20 minutes to obtain a solution B; adding octadecyltrimethylammonium bromide to deionized water, and subjecting the mixture to ultrasonic treatment for 10 to 20 minutes to obtain a solution C; Step 5: adding solution B and solution C to the suspension, stirring in a water bath for 5 to 7 hours, washing, centrifuging, filtering, drying, and grinding to obtain a modified filler; Step 6: After mixing polydimethylsiloxane, curing agent, epoxy resin and modified filler, add them into ethanol solution and stir for 50 to 70 minutes to form a uniform spray solution; Step 7: spray the spray liquid onto the surface of the plastic surface waterproof plywood, and cure it at 55-65° C. for 3-5 hours to form a hydrophobic coating on the surface of the plastic surface waterproof plywood to obtain a super hydrophobic plastic surface waterproof plywood.
7. A method for producing plastic-faced waterproof plywood according to claim 6, characterized in that: In step 2, the weight ratio of sodium montmorillonite to anhydrous ethanol is 1:20-30, the weight ratio of ethyl orthosilicate to anhydrous ethanol is 1:20-30, the ultrasonic frequency is 1.2-1.6 MHz, the ultrasonic power is 400-600 W, and the magnetic stirring speed is 400-600 r / min; in step 3, the weight ratio of mixture A to deionized water is 1:100-150, the ultrasonic frequency is 1.2-1.6 MHz, the ultrasonic power is 400-600 W, and the magnetic stirring speed is 400-600 r / min.
8. A method for producing plastic-faced waterproof plywood according to claim 7, characterized in that: In step 4, the weight ratio of octadecyltrimethoxysilane to anhydrous ethanol is 1:10-20, the weight ratio of octadecyltrimethylammonium bromide to deionized water is 1:10-20, the ultrasonic frequency is 1.2-1.6 MHz, and the ultrasonic power is 400-600 W; in step 5, the water bath temperature is 55-65° C., the stirring speed is 200-400 r / min, and the ethanol solution is used for multiple washings.
9. A method for producing plastic-faced waterproof plywood according to claim 8, characterized in that: In step six, the weight ratio of the total weight of polydimethylsiloxane, curing agent, epoxy resin and modified filler to the ethanol solution is 5.4-6.0:1; in step seven, the spraying pressure is 0.55-0.65 MPa.
10. The method for producing plastic-faced waterproof plywood according to claim 9, characterized in that: In step 2, the weight ratio of sodium montmorillonite to anhydrous ethanol is 1:25, the weight ratio of ethyl orthosilicate to anhydrous ethanol is 1:25, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 3, the weight ratio of mixed material A to deionized water is 1:125, the ultrasonic frequency is 1.4 MHz, the ultrasonic power is 500 W, and the magnetic stirring speed is 500 r / min; in step 4, the weight ratio of octadecyltrimethoxysilane to anhydrous ethanol is 1:15, the weight ratio of octadecyltrimethylammonium bromide to deionized water is 1:15, the ultrasonic frequency is 1.4 MHz, and the ultrasonic power is 500 W; in step 5, the water bath temperature is 60°C, the stirring speed is 300 r / min, and ethanol solution is used for multiple washings during washing; in step 6, polydimethylsilane The weight ratio of the total weight of the epoxy resin, curing agent, epoxy resin and modified filler to the ethanol solution is 5.7:1; in step seven, The spraying pressure is 0.60MPa.
Citation Information
Patent Citations
Plastic-covered plywood building formwork and preparation method thereof
CN106320695A
Preparation method of montmorillonite / sol-gel composite coating
CN113372813A
Durable super-hydrophobic anticorrosive coating and preparation method thereof
CN116120808A
Montmorillonite-based super-hydrophobic composite coating preparation method and coating thereof
CN117567921A
Shuttering made of novel composite material and process for making the same
CN1464156A
Cited By
Geopolymer-based ultraviolet-proof super-hydrophobic coating for engineering bamboo surface and preparation method of geopolymer-based ultraviolet-proof super-hydrophobic coating
CN120484539A
Antistatic PET dust-free film and preparation method thereof
CN120944158A
